Assistance in the Development of the Mulyaharja Organic Agro-Edu-Tourism Village (AEWO), Bogor City: Community Empowerment Strategy and Village Tourism Sustainability - Bambang Hengky Rainanto; Cecilia Valentina Srihadi Suryanti; TB Dicky Faldy; Septian Cahyadi; Charles Parnauli Saragi; Nisa Rahmaniyah Utami; Tarida Marlin Surya Manurung; Sri Endah Yuwantiningrum; Juke Sjukriana; Cinta Amanda Ally; Intan Wulandari; Cecilia Dwi Santati; Azzahra Liani Wazis (Universitas Ibn Khaldun, 2026)
The Mulyaharja AEWO (Organic Agro-Edu-Tourism) tourism village in Bogor City is a developed tourism village that integrates organic farming education, environmental conservation, and local economic empowerment. Community Service (PKM) mentoring is carried out by academics and the government to improve community capacity, attraction management, tourism product diversification, and digital promotion. The PKM method uses a participatory approach, including socialization, managerial training for managers, training in typical/traditional culinary processing, MSME training, homestay socialization and standardization, exploration of village tourism potential, and social media training as a promotional tool. The mentoring results show an increase in human resource capacity, service quality, tourism product diversification, implementation of homestay standards, digital promotion capabilities, and awareness of environmental sustainability. The impacts of PKM include local economic growth, community empowerment, cultural and environmental preservation, and the development of independent and educational tourism villages. This paper presents an effective community participation-based PKM model for the development of sustainable tourism villages in Indonesia.